Paramedic Differentiation of Asthma and COPD in the Prehospital Setting Is Difficult. (2nd October 2015) - Williams, Teresa A.; Finn, Judith; Fatovich, Daniel; Perkins, Gavin D.; Summers, Quentin; Jacobs, Ian
Abstract: Introduction . Separate clinical practice guidelines (CPG) for asthma and chronic obstructive pulmonary disease (COPD) often guide prehospital care. However, having distinct CPGs implies that paramedics can accurately differentiate these conditions. We compared the accuracy of paramedic identification of these two conditions against the emergency department (ED) discharge diagnosis.Methods . A retrospective cohort of all patients transported to ED by ambulance in Perth, Western Australia between July 2012 and June 2013; and identified as "asthma" or "COPD" by paramedics. We linked ambulance data to emergency department discharge diagnosis.Results . Of 1, 067 patients identified by paramedics as having asthma, 41% had an ED discharge diagnosis of asthma, i.e., positive predictive value (PPV) = 41% (95% CI 38–44%). Of 1, 048 patients recorded as COPD, 57% had an ED discharge diagnosis of COPD (PPV 57%; 95% CI 54–60%). Sensitivity for the paramedic identification of patients diagnosed with asthma or COPD in the ED was 66% for asthma (95% CI 63–70%) and 39% for COPD (95% CI 36–41%). Paramedics reported wheezing in 86% of asthma and 55% of COPD patients.Conclusion . Differentiating between asthma and COPD in the prehospital setting is difficult. A single CPG for respiratory distress would be more useful for the clinical management of these patients by paramedics